EXPERIMENT ON LONG-STORAGE OF FOOD PRODUCTS FOODSTUFFS IN CODITION OF PERMAFROST CONTINUED, ARCTIC, 2016 - S. E. Ulanin; S. L. Beletskiy (Овощи России, 2017)
In 1973 the crew of polar expedition, investigating the Middendorff Bay at the messdeck Zarya, discovered the depot of food products hidden in permafrost by head of Russian polar expedition E. Toll in 1900. There were oat flakes ‘Gerkules’ and croutons in the depot. Then the study carried out in Research Institute of Vegetable Drying and Can Industry had shown that all products discovered had preserved all their food qualities. That result leaded to launch up the experimental work on the possibility of preservation of food products and foodstuffs in permafrost till 2050. Quality of product found out in Taymyr Peninsula was analyzed. The results of study on qualities after long preservation in permafrost of such food products and foodstuffs as meat, milk, fish, confectionery, concentrated food, plant seeds were given. As a result of expedition in 2016, 20 samples were taken out and new samples of two types of products were placed into repository. Overall products placed consisted of 23 items, including foodstuffs and plant seeds with account of taking them out in 2025, 2035 and 2050. On the basis of research carried out, it is proved that most of modern and casual food products can be preserved without losing their quality values.